Stroke survivors’ perspectives on the selection of a post-acute care setting, rehabilitation goal-setting, and satisfaction with post-acute care rehabilitation, and transition to home - Krishnan, Shilpa (J Neurol Phys Ther, 2019)
BACKGROUND AND PURPOSE: Patients and caregivers have not typically been involved in the selection of a post-acute care (PAC) provider. In 2015, the Centers for Medicare and Medicaid Services (CMS) proposed the need to involve patients and their families during discharge planning. Engaging patients in rehabilitation decisions encourages shared decision-making among patients and their clinicians. The purpose of this study was to examine stroke survivors’ perspectives on their involvement in selecting a post-acute care (PAC) provider and their goal-setting, and their satisfaction with the rehabilitation stay, and their discharge advice for stroke survivors, prior to 2015. METHODS: This qualitative study utilized semi-structured interviews. Thematic content analysis was performed on 18 stroke survivors’ interviews (mean age=68 years) on their involvement related to their inpatient rehabilitation facility (IRF) or skilled nursing facility (SNF) stay, goal-setting, and discharge needs. RESULTS: More than half the participants were not involved in the selection of their PAC setting and believed that doctors made these decisions. Around two-fifths of stroke survivors reported they were not involved in rehabilitation goal-setting. Most patients were satisfied with their rehabilitation stay. When asked to recommend discharge topics for other stroke survivors, participants recommended additional information on health care services, interventions, and insurance coverage. CONCLUSION: Despite recommendations to include stroke patients in PAC selection and goal-setting, many former IRF and SNF patients report not being involved in either aspect of care.